Analisis Semantik Pada Puisi “Aku Ingin” Karya Sapardi Djoko Darmono: The Analysis of Semantics on The Poetry “Aku Ingin” From Sapardi Djoko Darmono - Kristianti, Ola; Sulastri, Saptiana (Kibas Cenderawasih, 2024)
This study aims to describe and find out about semantic studies that focus on grammatical meaning, lexical meaning, referential meaning and figurative meaning in the poem "I want" by Sapardi Djoko Darmono. In this study the authors used a descriptive method with a qualitative form, the data collection technique in this study was in the form of library techniques by utilizing various written sources to find data. The results and discussion are examining the grammatical meaning, lexical meaning, referential meaning and figurative meaning in the poem "I want" by Sapardi Djoko Darmono.